REMARKS ON ANTONI WĘGRZYNOWICZ’S MANUSCRIPT OF COLLECTED SERMONS ENTITLED SYLLABUS MARIANUS - Kuran, Magdalena (Prace Polonistyczne, 2021)
The article analyses the manuscript of collected sermons entitled Syllabus Marianus and written by the baroque preacher Antoni Węgrzynowicz. The manuscript provides an insight into Węgrzynowicz’s work as a preacher and serves as a source of biographical information. Based on the changes that the preacher made to the epigrams (which are a typical element of the sermons), the article argues that Węgrzynowicz himself was their author (so far, these works have been regarded as fragments of Marian hymns). The manuscript also includes two pages that are unrelated to the collection. One of them features an outline of the sermon that Węgrzynowicz preached to his confreres on the feast of Christmas in 1715. These notes also reveal some tricks of the preacher’s art. The information that the second sheet contains gives insight into the everyday life in an 18th-century monastery.